A structured review of mobile augmented reality for language instruction and learning - Mat Sa’ud, Asmah; Md Ghalib, Mohd. Feham; Abu Bakar, Radhwa (Global Academic Excellence (M) Sdn Bhd (GAE), 2023)
Mobile technology has revolutionized various aspects of our lives, including education. With the rapid advancement of mobile devices and their increasing accessibility, educators have begun exploring new and innovative ways to enhance learning experiences. One such innovation is the integration of augmented reality (AR) applications into education. However, there is still limited research about teaching and learning in a foreign language. Therefore, the present study discusses the potential of AR technology in teaching as an educational tool, specifically for language teaching and learning. Thus, this paper employed the method of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) to highlight the potential of AR technology as an educational tool. Advanced searching has been used through Scopus and Web of Science (WoS) databases were the main platforms for sources for articles. Based on the search results, we found (n=25) published articles that associated AR in language instruction and learning were extracted out of (n=705), from 2022 to 2023. Expert scholars decided to develop three themes which are (1) the type of platforms used for mobile augmented reality (MAR) applications in language instruction and learning, (2) the language proficiencies focused on MAR applications, and (3) the impacts of MAR applications on language instruction and learning. By showcasing MAR's potential to motivate and engage learners, this paper underscores its significance in modern language education.